Autonomy in language education theory, research and practice - Jiménez Raya, Manuel; Vieira, Flávia (Routledge, 2021)
Autonomy in Language Education offers a holistic overview of and novel contribution to a complex and multifaceted, yet under-studied, field of inquiry that is transforming language pedagogy: It offers nineteen original chapters that critically analyze the impact of Henri Holec's seminal 1979 book Autonomy in Foreign Language Learning; unpack theoretical, empirical, conceptual, methodological, ethical, and political developments over the last forty years from many perspectives; explore practical implications for teaching, learning, and teacher education; and suggest future avenues and challenges for research and practice in this broad, diverse, essential field
Description based on online resource; title from digital title page (viewed on July 24, 2020)
Keywords: Holec, Henri / Autonomy and foreign language learning; Learner autonomy; Language and languages / Study and teaching